A cryptographic application of the Thurston norm. Issue 1 (2nd January 2020) - Flores, Ramón; Kahrobaei, Delaram; Koberda, Thomas
Abstract : We discuss some applications of 3-manifold topology to cryptography. In particular, we propose a public-key and a symmetric-key cryptographic scheme based on the Thurston norm on the first cohomology of hyperbolic manifolds.